2021
DOI: 10.3389/fcvm.2021.674471
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification for Atrial Fibrillation and Outcomes in Tachycardia-Bradycardia Syndrome: Ablation vs. Pacing

Abstract: Background: Catheter ablation of atrial fibrillation is an alternative treatment for patients with tachycardia-bradycardia syndrome (TBS) to avoid pacemaker implantation. The risk stratification for atrial fibrillation and outcomes between ablation and pacing has not been fully evaluated.Methods: This retrospective study involved 306 TBS patients, including 141 patients who received catheter ablation (Ablation group, age: 62.2 ± 9.0 months, mean longest pauses: 5.2 ± 2.2 s) and 165 patients who received pacema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…A total of four studies, [21][22][23][24] all retrospective single centre cohorts, fulfilled all inclusion criteria (Table 1). Baseline study variables are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A total of four studies, [21][22][23][24] all retrospective single centre cohorts, fulfilled all inclusion criteria (Table 1). Baseline study variables are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The present meta-analysis involved 5 studies [16–20] encompassing approximately 843 individuals, and revealed 4 significant findings. First, catheter ablation was found to lower the risk of stroke, and heart failure in comparison to pacemaker implantation.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, a total of 5 studies, involving 843 participants, met the inclusion criteria and were used in the meta-analysis. [16][17][18][19][20] The flow diagram illustrating the process of searching and screening publications is presented in Figure 1. The characteristics of the included studies are summarized in Table 1.…”
Section: Studies Retrieved and Characteristicsmentioning
confidence: 99%
“…(9) En cambio, en el STB el manejo y el tratamiento de primera línea es la implantación del marcapaso en el 30 % al 50 % de los casos, (2) pudiéndose evitar o reemplazar con ablación por catéter en más del 85 % de los pacientes con FA, evitando las infecciones o miocardiopatías provocadas por el marcapaso. (3) La ablación por catéter disminuye: la sintomatología, la tasa de mortalidad, hospitalizaciones, ACV, trombosis periférica, insuficiencia cardíaca y la conversión a FA persistente. (10) El pronóstico de la ablación por catéter; según Hada et al (11) , en 65 pacientes con 3 años de seguimiento, obtuvieron una tasa de éxito del 80,6 % en el tratamiento; igualmente Kim et al (12) en una muestra de 121 participantes con STB, demostraron que el 90,9 % no requirieron de un implante de marcapasos.…”
Section: Discussionunclassified
“…(2) La entidad clínica que incorpora un BIAa con la aparición consecutiva de taquiarritmias supraventriculares (TS), comúnmente flutter auricular o fibrilación auricular (FA), se denomina Síndrome de Bayés. (1) El STB, como parte de la ENS, se presenta como pausas sinusales significativas (mayor a 3 segundos) posterior a un evento paroxístico de taquicardia supraventricular, en especial flutter o fibrilación auricular (3) que pueden llevar al desarrollo de síncope. (2) El Síndrome de Bayés y el STB, tienen como mecanismo común al daño estructural y funcional de la aurícula izquierda (AI).…”
Section: Introductionunclassified